Nanoparticle Formulations of Poly (ADP-ribose) Polymerase Inhibitors for Cancer Therapy - Singh, Bijay; Yang, Shicheng; Krishna, Apurva; Sridhar, Srinivas (Frontiers in Chemistry, 2020)
A number of poly(ADP-ribose) polymerase (PARP) inhibitors have been recently approved for clinical use in BRCA mutated and other cancers. However, off-target toxicity of PARP inhibitors and the emergence of drug resistance following prolonged administration indicates the need for improved methods of delivery to the tumors. Nanomedicines based upon nanoparticle formulations of conventional small molecule drugs and inhibitors offer many advantages, such as increased solubility and bioavailability of drugs, reduced toxicity and drug resistance, and improved tissue selectivity and therapeutic efficacy. This review highlights the current trends in formulations of PARP inhibitors developed by nanotechnology approaches and provides an insight into the applications and limitations of these PARP inhibitor nanomedicines for cancer therapies.